Democratic Discontent in Old and New Democracies: Assessing the Importance of Democratic Input and Governmental Output. (28th October 2014) - Dahlberg, Stefan; Linde, Jonas; Holmberg, Sören
Abstract : Although the phenomenon of dissatisfied democrats has been frequently discussed in the literature, it has not often been empirically investigated. This article sets out to analyse the discrepancy between the strong support for democratic principles and the widespread discontent with the way democracy works. Drawing on earlier research on the sources of political support, using data from a wide range of democracies, the relevance of two contrasting explanatory perspectives are investigated. The first perspective argues that the sources of democratic discontent are found on the input‐side of the political system in terms of representation. The contrasting view argues that the output‐side of the political system is most important, where the quality of government plays the pivotal role. The results of the empirical analysis suggest that, in general, both types of factor are important, but also that these processes to a large extent are conditioned by the level of institutional consolidation.